Statement of the Financial Economists Roundtable: Crowdfunding. Issue 4 (1st July 2016) - Conrad, Jennifer; Karpoff, Jonathan; Lewis, Craig; Ritter, Jay R.
Abstract : The Financial Economists Roundtable, a group of distinguished senior financial economists, discusses current issues and future developments in the crowdfunding market and offers suggestions regarding the regulation of the industry. Abstract : Editor's note: This article was reviewed and accepted by Executive Editor Stephen J. Brown. Authors' note: This statement is an outcome of the Financial Economists Roundtable discussion at its annual meeting on 18–20 July 2015 in Vancouver, British Columbia, Canada. It reflects a consensus of more than two-thirds of the attending members. Although the statement provides suggestions to the US Securities and Exchange Commission (SEC) for how to improve crowdfunding, the issues involved affect crowdfunding throughout the world. If adopted, these suggestions would improve crowdfunding globally.